Effect of Gamma Irradiation on Vegetative Growth of three Sugarcane Genotypes (Saccharum officinarum L.) in field (Baghdad Science Journal, 2011)
I n vitro rooting plantlets of three sugarcane genotypes(Co.j.64, Co.j.86 and Missan) were cultured in the field after exposed at different doses of gamma rays (1,2,3,4,) kr.Data of reduction percentage on vegetative growth, roots number, length per plant and their diameter were investigated.Results showed gradual reductions in number of shoots, length and diameter as according to increasing of gamma doses. The reduction percentage in shoot number, length were reached 57.86,70.36 % at 4 kr respectively which have mean number and length per plant reached (9.27 and 55.33 cm) as compared with the control treatment ,While 1 kr caused higher percent in diameter reached 9.69 % with mean of diameter per plant reached 2.57 cm.Mean time , Genotype were significant difference in reduction percent , Co .j.64 genotype surpassed in shoots length , diameter reached 120.78% , 62.15% respectively, Which have mean (204 cm/plant) and( 2.99cm/plant ) ,While Co.j.86 surpassed in number of shoots reached 16.44% .